Chemical composition and biological activities of the species capsicum frutescens l. (chili pepper) – A literature review - Santos, Vinicius Almeida; Santos, Richardson Alves; da Silva, Eduardo Santos; Alves, Amanda Souza; Ferreira, Rafaela Oliveira; de Carvalho Junior, Almir Ribeiro (Seven Editora, 2023)
Peppers are known to have compounds that are responsible for some of their characteristics. One can find, for example, natural antioxidants, phenolic compounds, capsaicinoids, caretonoids, among other chemical components. Some of these compounds allow peppers to carry out important biological activities, so that some species of these fruits can be used for medicinal purposes. In this sense, the peppers that most stand out are those of the genus Capsicum, which have universal use and are widely produced and commercialized, this genus has about 30 species, among which is Capsicum frutescens (chili pepper), which is a of domesticated species. Thus, in view of its importance from a medicinal point of view, this work presents a literature review, gathering information on the chemical composition of chili pepper, pointing out several compounds, among which capsaicin, dihydrocapsaicin, phenolic compounds, acids fatty acids and vitamin C. The biological activities reported for the species are also highlighted, such as antioxidant, antimicrobial, analgesic and anti-inflammatory, among others. Thus, it was verified the great potential of this pepper in the realization of beneficial effects to health and the importance of carrying out more studies regarding the attributes of this fruit.DOI:https://doi.org/10.56238/alookdevelopv1-167